Data Mining Using the K-Means Clustering Method Can be Applied to Determine Production Amounts Based on Product Sales Data at PT. Coca Cola Distribution Indonesia Bengkulu - Rozzi, Yoli Andi (International Journal of Artificial Intelligence Research, 2023)
This research applies data mining using clustering method for determining the amount of production is based on the level of product sales at PT . Coca Cola Distribution Indonesia Bengkulu branch . The algorithm used is the K -Means Clustering , where the data are grouped by similar characteristics will be included in the same group and a set of data entered into non-overlapping groups . Information displayed in the form of a group - a group of product data based on the level of sales , in order to know the amount of production in PT.Coca Cola Distribution Indonesia tailored to cluster products with sales levels high, medium and low. The testing of this research is using RapidMiner 5.3, so it will gain some clusters who really helpful for PT.Coca Cola Distribution of Indonesia in determining the number of next production